2019
DOI: 10.1111/aej.12354
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different voxels and exposure parameters of CBCT for the assessment of external root resorptions: A phantom study

Abstract: This study aimed to compare the effectiveness of the different voxel sizes and imaging parameters of cone beam computed tomography (CBCT) on the determination of external root resorption (ERR). ERRs were created in coronal, middle and apical regions. Depths (0.62-0.73 mm) and diameters (0.68-0.81 mm) of ERRs were measured using a digital calliper. Images were obtained in 0.125, 0.2, 0.25, 0.3 and 0.4 mm 3 voxel sizes and at different currents. Data were analysed using Friedman and Wilcoxon signed-rank tests at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Only when ERR is detected in the initial stage can the affected tooth be treated by repairing the resorption cavity with no pulpal injury. The detection of ERR in the later stage unfavorably alters the prognosis and might result in root canal treatment or tooth extraction [ 11 , 26 ]. Some researchers have thought of using ERR markers in saliva and gingival cervical fluid as an alternative to traditional methods because they thought that classical radiography methods were insufficient to diagnose ERR in the early stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only when ERR is detected in the initial stage can the affected tooth be treated by repairing the resorption cavity with no pulpal injury. The detection of ERR in the later stage unfavorably alters the prognosis and might result in root canal treatment or tooth extraction [ 11 , 26 ]. Some researchers have thought of using ERR markers in saliva and gingival cervical fluid as an alternative to traditional methods because they thought that classical radiography methods were insufficient to diagnose ERR in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Ponder et al [ 33 ] reported that a voxel size of 0.2 mm 3 was more accurate than one of 0.4 mm 3 to detect the different sizes (1 mm and 1.8 mm) of ERR cavities. Goller-Bulut and Ugur-Aydin [ 26 ] also reported that decreased voxel size gave more accurate results in middle and coronal region ERR measurements. However, the authors did not find a significant difference in voxel sizes for the diameter and depth of the apical ERRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this voxel size is not classified as high resolution, studies about root resorption found no statistic differences when smaller voxels were used, particularly when resorption is in the apical third of the root. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Only a proportion of patients may benefit from a change in the treatment plan as a consequence of ERR, and therefore, the evidence-based indications for the use of CBCT for diagnosis are currently limited to particular cases ( 19 ). Consequently, the decision as to whether to use high-resolution, radiation-dose CBCT protocols to diagnose a clinically irrelevant amount of ERR should be based on sound assessment of the risk/benefit ratio for the patient ( 6,19,45 ).…”
Section: Protocol For Imagenological Control Of Errmentioning
confidence: 99%